REPRESENTATION OF CHARACTER EDUCATION IN ENGLISH TEXTBOOKS HIGH SCHOOL LEVEL: CRITICAL DISCOURSE ANALYSIS - Fajari, Alka; Ulfya, Siti (Journal of English Education and Teacher Trainer, 2024)
This research investigates the representation of character education values in online English textbooks used in secondary schools. Online textbooks that are aligned with the latest curriculum function as a fundamental source in instilling values, especially character education using critical discourse analysis. Research findings show that discipline, friendship/communicativeness, and fostering a love of reading emerge as the most prominent values. This research seeks to complement existing literature by offering insight into the representation of character education content in English textbooks used in elementary schools throughout Indonesia.